Decidere per chi non può Approcci filosofici all'eutanasia non volontaria - Matteo Galletti (Studi e saggi, 2005)
For centuries, philosophical debate has focused on concepts such as "person", the "value" and "quality" of life, "rights", "suffering", "life" and "death". However, the problems that have emerged over the last decades as a result of the application of life-extending technologies have led to a reconsideration of both the philosophical and the everyday usage of such concepts. This book is intended as a reflection on certain aspects of the debate on the moral legitimacy of non-voluntary euthanasia, through a critical discussion of the principal philosophical notions utilised in bioethics.